A proof‐of‐concept study on the effects of low total cfDNA content and solutions to increase the NIPT trisomy 21 detection rate. Issue 2 (30th September 2019) - Du, Yang; Chen, Ailing; Yang, Rui; Zhou, Tao; Zhou, Qin; Yang, Lan; Wang, Juan; Hong, Yan; Chen, Chen; Wan, Qian; Yang, Lin; Chen, Ying
Abstract: Background: Non‐invasive prenatal testing (NIPT) is routinely used in clinical practice for fetal trisomy screening, but low total cfDNA content and low fetal fraction (LFF) are two factors that affect the detection rate. Samples with low total cfDNA or LFF usually end up with "no‐call" results, followed by the blood redraw and re‐testing, which is inconvenient for pregnant women and clinicians. Methods: We created mock trisomy 21 (T21) samples to investigate the effects of low total cfDNA with low LFF and possible solutions to increase their detection rate. Results: Samples with low total cfDNA resulted in the decreased unique reads number and increased duplication rate. Abnormal correlations between library concentration and raw reads number and the coverage fluctuation value, ZsdNorm, were also discovered, suggesting that low total cfDNA could lead to the overestimation of the library concentration. Additionally, a non‐reference‐based derivative value method (DV method) was evaluated and the data demonstrated that the detection sensitivity of trisomy 21 was increased from 33.33% (6/18) to 94.44% (17/18) in samples with 5% fetal fraction comparing with the z ‐score approach, whereas for LFF (3.5%) group, the performance was raised from 0% to 35.29% (6/17). Conclusion: Low total cfDNA has significant impacts on NIPT performance by altering sequencing quality. The non‐reference‐based DV method could increase the T21 detection rate in samples with limited cfDNA content and 5% fetal fraction, but it was not as effective for those with LFF.